'A model for the country': letters from Florence Nightingale to the architect, Thomas Worthington, on hospitals and other matters 1865–1868. Issue 2 (18th December 2012) - Butler, Stella Vera F
Abstract : Between 1865 and 1868 the Manchester architect, Thomas Worthington and Florence Nightingale corresponded about hospital design. Worthington was involved in building hospitals for two Poor Law Unions in Manchester. The designs of both hospitals were based on the 'pavilion' principle of which Nightingale became a vocal national champion. Through five letters written by Nightingale to Worthington, the paper explores Nightingale's views focussing on her admiration for the designs, and examines the importance of these commissions for Worthington's career as a hospital architect.